“EFFECTIVENESS OF VIDEO ASSISTED TEACHING PROGRAM REGARDING KNOWLEDGE AND PRACTICE REGARDING BIOMEDICAL WASTE MANAGEMENT GUIDELINES AMONG BIOMEDICAL WASTE HANDLERS” - R. Jadhav, Poonam; B. Zagade, Tukaram; Gholap, Manisha; B Shinde, Mahadeo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Iny-to-day life, most of the biomedical waste handlers are unaware of the newer guidelines from 2016. There is a need for training regarding the newer 2016 guidelines on biomedical waste management for biomedical waste handlers to improve their work efficiency and adoption of newer guidelines for the safe practice of biomedical waste management, thereby improving the safety exposed to the infectious and toxic waste of the hospital. Objective: 1. To assess the status of knowledge and practice among biomedical waste handlers regarding the new guidelines for 2016 biomedical waste management. 2. To assess the status of knowledge and practice of biomedical waste handlers regarding new guidelines of biomedical waste management after the learning package. Methods and materials: A one-group pretest-posttest research design was used, and samples were selected by using a non-probability purposive sampling technique. The sample size was 55 biomedical waste handlers and sweepers working in various wards and departments of BMWM KH and MRC, Karad. Before practices of handlers were observed and a pretest was conducted before administering video-assisted teaching and a structured lesson plan, a posttest was conducted after 7 days, and a post-observation was done. Results: The present study showed that pre-test mean score of total knowledge was 10.96 and post-test it was increased up to 18.72 and practice score was increased from 16.09 to 19.36. The paired‘t’ test was used for this study. The p value < 0.0001 which is considered to be Extremely Significant so it indicated that video assisted teaching programme was effective for improving knowledge and practices of biomedical waste handlers and there was significant association between age and gender and knowledge but there was no significant association with practice of biomedical waste handlers. There was a no significant association between education, income, experience and training and knowledge and practice regarding BMWM according to (2016) guidelines. Conclusion: Based on the analysis of findings it was shown that increase in the knowledge and practice scores of biomedical waste handlers after administration of video assisted teaching program.